Clinical Management of Facemasks for Early Treatment of Class III Malocclusion: A Survey among SIDO Members - Lorenzo Franchi; Michele Nieri; Patrizia Marti; Annamaria Recupero; Alessandra Volpe; Alessandro Vichi; Cecilia Goracci (MDPI AG, 2024)
To evaluate whether there are differences among orthodontists in the clinical management of facemask treatment for early treatment of Class III malocclusion, a survey consisting of 16 questions was conducted among members of the Italian Society of Orthodontics (SIDO). Sixty percent of the respondents were Specialists in Orthodontics (S) whereas 40% were General Dentists practicing Orthodontics (GD). Descriptive statistics were calculated to summarize the collected data. Differences in answers between S and GD were assessed with the Fisher's exact test for dichotomous variables, chi-square test for qualitative variables, and Mann-Whitney test for ordinal variables. A total of 151 clinicians participated in this survey. As for treatment timing, about 80% of the participants reported treating Class III patients with RPE and facemask between 5 and 8 years of age. Most of the participants requested the patients to wear the facemask in the afternoon and at night for a period of 9 or 12 months with recommended forces of 500 g per side. Comparisons between S and GD showed that S preferred the Petit facemask whereas GD favored the Delaire's type facemask (Fisher's Exact test, p = 0.0005). S and GD also differed significantly in their judgment of the most critical time of treatment, which for the majority of GD was the initial period but for the S was the final period (Chi-square test p = 0.0188). This survey showed that the facemask is not well received by the patients who, along with their parents, express concerns regarding its tolerability.